Instructional Change after Participating in a Mathematics Professional Development Program: An Exploration of Impact. Issue 1 (2nd January 2023) - Koellner, Karen; Seago, Nanette; Jacobs, Jennifer
Abstract: This research study explored teachers' self-reported uptake as well as observed instructional change after participating in a year-long professional development (PD) program focused on supporting the learning and teaching of transformations-based geometry. Analyses illuminate the degree and nature of the pedagogical shifts made by teachers who participated in this highly specified, videocase-based PD program. The treatment teachers' lessons started out significantly lower on most aspects of their instructional quality relative to the control teachers' lessons prior to the PD. However, the control teachers stayed the same or showed a decline in their instructional quality scores, whereas the treatment teachers made significant gains after the PD that brought them to the same level as the control teachers. The article concludes by considering how engagement with intentionally designed videocases during the PD may have contributed to the teachers' improvement in targeted dimensions of instructional quality.